Electricity, Neurology, and Noninvasive Brain Stimulation: Looking Back, Looking Ahead - Vijay Renga (Neurology Research International)
Electricity and neurology evolved synchronously over the past few centuries. This article looks at their origins and their journey into noninvasive brain stimulation technique of transcranial direct current stimulation (tDCS), which is now popular in neuroscience research.